A General Electro‐Synthesis Approach to Amaryllidaceae Alkaloids. Issue 50 (13th July 2022) - Pollok, Dennis; Großmann, Luca M.; Behrendt, Torsten; Opatz, Till; Waldvogel, Siegfried R.
Abstract: Amaryllidaceae alkaloids appeal to organic chemists with their attractive structures and their impressive antitumor and acetylcholinesterase inhibitory properties. We demonstrate a highly versatile access to this family of natural products. A general protocol with high yields in a sustainable electro‐organic key transformation on a metal‐free anode to spirodienones facilitates functionalization to the alkaloids. The biomimetic syntheses start with the readily available, inexpensive biogenic starting materials methyl gallate, O ‐methyl tyramine, and vanillin derivatives. Through known dynamic resolutions, this technology provides access to both enantiomeric series of (epi‐)martidine, (epi‐)crinine, siculine, and galantamine, clinically prescribed for the treatment of Alzheimer's disease. Abstract : Highly pharmaceutically relevant Amaryllidaceae alkaloids have been accessed by a versatile electro‐organic key transformation, including a precursor of the acetylcholinesterase inhibitor galantamine, used as FDA‐approved drug for the treatment of Alzheimer's disease. Spirodienone‐type intermediates were obtained in a regioselective and sustainable anodic key transformation from nature‐derived starting materials